(untitled) (Scientific journal of the Fergana State University, 2023)
This article highlights the scientific and methodological basis for the formation of communicative competence in the teaching of Russian language to students of non-linguistic universities. The experience of the researcher’s work on the development of communicative skills of university students is reflected. Types of communication. The main functions of communication